2021
DOI: 10.3389/fnagi.2021.695232
|View full text |Cite
|
Sign up to set email alerts
|

tDCS-Induced Memory Reconsolidation Effects and Its Associations With Structural and Functional MRI Substrates in Subjective Cognitive Decline

Abstract: Previous evidence suggests that transcranial direct current stimulation (tDCS) to the left dorsolateral prefrontal cortex (l-DLPFC) can enhance episodic memory in subjects with subjective cognitive decline (SCD), known to be at risk of dementia. Our main goal was to replicate such findings in an independent sample and elucidate if baseline magnetic resonance imaging (MRI) characteristics predicted putative memory improvement. Thirty-eight participants with SCD (aged: 60–65 years) were randomly assigned to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Importantly, a recent study ( Vaqué-Alcázar et al, 2021 ) replicated our findings ( Manenti et al, 2017 ) in an independent sample, which confirmed that tDCS, through the modulation of memory reconsolidation, is capable of enhancing performance in people with SMC. This study also suggested that individuals with more preserved structural and functional integrity might benefit from this intervention.…”
Section: Introductionsupporting
confidence: 86%
“…Importantly, a recent study ( Vaqué-Alcázar et al, 2021 ) replicated our findings ( Manenti et al, 2017 ) in an independent sample, which confirmed that tDCS, through the modulation of memory reconsolidation, is capable of enhancing performance in people with SMC. This study also suggested that individuals with more preserved structural and functional integrity might benefit from this intervention.…”
Section: Introductionsupporting
confidence: 86%
“…Enhanced rsFC of the brain has been suggested as the mechanistic basis for the effects of other NIBS, such as tDCS and TMS, in depression, schizophrenia, and dementia [54][55][56][57]. An increase in rsFC in the default mode network (DMN) was also noted following PBM in stroke [22] and dementia [30].…”
Section: Discussionmentioning
confidence: 99%
“…An RCT measuring the effect of a combined transcranial direct current stimulation (tDCS) and mindfulness‐based stress reduction in individuals with SCD found that although feasible and safe, there were no statistically significant effects on outcome measures (i.e., mindfulness, social functioning, mood, subjective cognition and objective cognitive performance) compared to combined sham tDCS with mindfulness‐based stress reduction 149 . A double‐blind tDCS versus sham study found that individuals with SCD who had greater structural and functional brain integrity (per MRI) had the greatest tDCS‐induced memory consolidation effect, indicating these individuals may benefit most from this form of neuromodulation 150 . A study of repeated transcranial magnetic stimulation in older adults with SCD found evidence of enhanced visual working memory, and significantly improved attention and executive function when the left dorsolateral prefrontal cortex was stimulated 151 …”
Section: Interventions In Scdmentioning
confidence: 95%
“…149 A doubleblind tDCS versus sham study found that individuals with SCD who had greater structural and functional brain integrity (per MRI) had the greatest tDCS-induced memory consolidation effect, indicating these individuals may benefit most from this form of neuromodulation. 150 A study of repeated transcranial magnetic stimulation in older adults with SCD found evidence of enhanced visual working memory, and significantly improved attention and executive function when the left dorsolateral prefrontal cortex was stimulated. 151 In sum, data on recent interventions in SCD have been mixed.…”
Section: Neuropsychiatric Symptoms In Scdmentioning
confidence: 99%